Intonation of Wh-questions in Northern British English Spontaneous Speech - Sola, Alicia; Torregrosa-Azor, José (International Journal of English Studies, 2023)
In this paper, we report the analysis of the melodic behavior of wh-questions from the North of England. The corpus contains 107 utterances issued by 19 different native informants in real communicative situations, extracted from recordings of street interviews published on YouTube and carried out in the cities of York, Manchester, Sheffield and Liverpool. The analysis is conducted through the Melodic Analysis of Speech (MAS) method (Cantero, 2002) which allows us to quantify, standardize and compare melodic configurations. The results describe four different intonation patterns for this type of question. A rising final inflection pattern (E1: 27%); a falling final inflection pattern (E2: 58%); a circumflex rising-falling final inflection pattern (E3: 5%); and a high nucleus falling pattern (E4: 10%). After describing and quantifying each of these patterns, the results are discussed in relation to those melodic descriptions made by precedent authors in the existing literature.